1999
DOI: 10.1111/j.1751-1097.1999.tb08248.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Transitions of Singlet Oxygen: New Tools, New Techniques and New Interpretations

Abstract: The near-IR phosphorescence of singlet delta oxygen, O2(a1Ap), has provided a wealth of information since it was first observed in solution-phase systems. The techniques employed and the quality of the data obtained have improved significantly over the years that, in turn, presently makes it possible to address a wide variety of problems using both steady-state and time-resolved measurements. The development of spectroscopic methods to monitor other transitions in oxygen, specifically those that involve the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 57 publications
2
66
0
Order By: Relevance
“…In earlier publications, we reported that the a-b Stokes shift in CS 2 was ∼10 cm -1 . 1,11,12 Although this shift is still quite small, this early determination appears to have been adversely influenced by a number of experimental factors associated with the use of a FTIR to detect emission [e.g., sample position and optics at collection port (see Experimental Section)]. A more accurate value for the a-b Stokes shift in CS 2 is the ∼3 cm -1 reported herein.…”
Section: Experimental and Computational Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…In earlier publications, we reported that the a-b Stokes shift in CS 2 was ∼10 cm -1 . 1,11,12 Although this shift is still quite small, this early determination appears to have been adversely influenced by a number of experimental factors associated with the use of a FTIR to detect emission [e.g., sample position and optics at collection port (see Experimental Section)]. A more accurate value for the a-b Stokes shift in CS 2 is the ∼3 cm -1 reported herein.…”
Section: Experimental and Computational Methodsmentioning
confidence: 81%
“…12 In all cases, both the O 2 (b 1 Σ g + ) and O 2 (a 1 ∆ g ) states of oxygen were created upon pulsed-laser irradiation of a singlet oxygen photosensitizer. The laser (Quanta-Ray GCR 230 Nd:YAG) was operated at a 10 Hz repetition rate, and the irradiation wavelength was tuned throughout the UV/vis region using (1) the second, third, and fourth harmonics of the Nd:YAG fundamental output, (2) an optical parametric oscillator whose output could also be doubled, and/or (3) a high-pressure cell of H 2 gas as a Raman shifting medium.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrumentation and methods used to (1) monitor O 2 (a 1 D g ) ? O 2 (X 3 Σ g À ) phosphorescence at~1275 nm in time-resolved experiments and quantify photosensitized O 2 (a 1 D g ) quantum yields and O 2 (a 1 D g ) lifetimes (21)(22)(23), and (2) perform time-resolved triplet absorption experiments (22) are described in the references cited. For the O 2 (a 1 D g ) studies, miniSOG was irradiated with the 1 kHz output of a fs laser at 418 nm, and all O 2 (a 1 D g ) experiments were performed in 1 cm path length cuvettes under conditions where the sample absorbance at the irradiation wavelength did not exceed~0.1.…”
Section: Introductionmentioning
confidence: 99%
“…In almost all cases, it is also necessary to account for the response time of the laseddetection system. A more detailed discussion of these issues in the analysis of time-resolved O,(blZ,+) data is given in a second paper in this journal issue (15).…”
Section: Nonradiative Decaymentioning
confidence: 99%